El trabajador social como educador: formación profesional y educación - Argumedo, Manuel Alberto (2001)
In this research work, the relations between Social Work and Education are analysed, from considering that, in some situations of intervention, the educational action itself constitutes a resource for the social worker. Our questionis, in this case, to what extent the Institutions of Formation are worried about whether their students consider this option and have lhe necessary elements to design, to execute and to evaluate an educational action. It also interests us to know, in case it happens, which is the conception of education that those futures social working have. With this purpose, a definition of education, like intentional action that it prometes certain and determined leaming in other people, it is tried to formulate. Different "intentions" that permit so many other "modes" of educating are analysed and a form to analyse educational actions that would put in evidence lhe principles or criteria that orient them is broached. In order to finalize this part of lhe work, lhe conception of education, from which the analysis is made, is exposed and the principIes that serve as foundation are enunciated. In order to complete this operative referential of lhe research, the profession of the social worker in our world is briefly analysed. Before presenting the field work, some reflections on key methodological concepts in the research, like social representations, are made. In this context, and taking care of lhe objective of lhe research, it is opted for the term "believing /creencias", in the sense of a set or array of "convictions/convicciones" that constitutes the conception of educational action from which the educator works. Finally some inquiries made at level of institutions of formation and people that have decided on the profession of the social work are submitted. In the first case, curricula of institutions with different reference frameworks and interviews to directorate and professors of the career are analysed. In lhe second case, interviews to pupils of recent entering to the university/ingresantes, recent graduates and social workers in activity and the results of a test of resolution of cases applied to students who attend the last years of their career are analysed. These analyses allow to formulate some conclusions on lhe commonest "mode" to educate privileged by the social workers and some recommendations on lhe professional formation are suggested